Hydrogen sulfide suppresses outward rectifier potassium currents in human pluripotent stem cell-derived cardiomyocytes. - Heming Wei (Public Library of Science (PLoS), 2012)
Aim Hydrogen sulfide (H₂S) is a promising cardioprotective agent and a potential modulator of cardiac ion currents. Yet its cardiac effects on humans are poorly understood due to lack of functional cardiomyocytes. This study investigates electrophysiological responses of human pluripotent stem cells (hPSCs) derived cardiomyocytes towards H₂S. Methods and results Cardiomyocytes of ventricular, atrial and nodal subtypes differentiated from H9 embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs) were electrophysiologically characterized. The effect of NaHS, a donor of H₂S, on action potential (AP), outward rectifier potassium currents (I(Ks) and I(Kr)), L-type Ca²⁺ currents (I(CaL)) and hyperpolarization-activated inward current (I(f)) were determined by patch-clamp electrophysiology and confocal calcium imaging. In a concentration-dependent manner, NaHS (100 to 300 µM) consistently altered the action potential properties including prolonging action potential duration (APD) and slowing down contracting rates of ventricular-and atrial-like cardiomyocytes derived from both hESCs and hiPSCs. Moreover, inhibitions of slow and rapid I(K) (I(Ks) and I(Kr)), I(CaL) and I(f) were found in NaHS treated cardiomyocytes and it could collectively contribute to the remodeling of AP properties. Conclusions This is the first demonstration of effects of H₂S on cardiac electrophysiology of human ventricular-like, atrial-like and nodal-like cardiomyocytes. It reaffirmed the inhibitory effect of H₂S on I(CaL) and revealed additional novel inhibitory effects on I(f), I(Ks) and I(Kr) currents in human cardiomyocytes.